STRATEGIES FOR EFFECTIVE READING CORNER MANAGEMENT TO INCREASE STUDENTS' INTEREST IN READING AT LAPANG BARU PUBLIC ELEMENTARY SCHOOL - Fanpada, Nehemia; Maarang, Yane; Maleipen, Yohanis; Hingmo; Lauata, Semuel; Tekamaki, Maryos Abia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students' interest in reading is very important in education. One strategy to increase students' interest in reading is to provide a reading corner in schools. The purpose of this study was to determine the reading corner management strategies used by schools to increase students' interest in reading at SD N Lapang Baru, Kuifana Village, South Abad District. The problem found in the field was the low interest in reading among students at the school. The method used in this study was qualitative descriptive. The results showed that students were very enthusiastic about visiting the reading corner to read the books provided there, and some students also wrote summaries of their subjects in the reading corner area. They did this activity for 15 minutes before starting class, filling their free time when the teacher was not in class, and during recess, students were free to choose reading books that were provided in the reading corner. If there was something they did not understand, the students immediately asked their friends or the teacher about it. In addition, there were some students who were very enthusiastic about reading and writing but still needed guidance from the teacher. Guidance for some students specifically to improve their literacy skills can be seen in the following picture.